Mengembangkan Rasionalitas dalam Beragama Melalui Penerapan Ilmu Manṭiq (Sebuah Upaya Menangkal Radikalisme dalam Paham Keagamaan) - Basrir Hamdani (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2021)
To put forward the rationality based on logical (manṭiq) principles in embracing religion constitutes an attempt to approach the truth, if not to say to grasp the truth, in understanding authentically the teachings of religion which are stated in holly scriptures (al-Qur’an and al-Hadits) based on the principle of religion itself, i.e., to present the virtues and salvation wether in this world and hereafter. This is at once a reason to avoid the textual-formalistical understanding toward the holly scriptures, since it tends to ram one holly scripture to one other and in implication toward religious behavior, it triggers frictions and collisions among heterogeneous peoples. In such a way, it has brought frequently to radicalism. This research aims at analyzing the importance of evolving the rationality in embracing religion by means of practicing Logics (‘Ilm al-Manṭiq) as one of the alternative ways for deradicalization of religius understandings. This research is conducted through analytical-descriptive method wether in investigation or in elaborating the data which are found in many literatures and in the form of library research.